Compositional and spectroscopic investigation of three ungrouped carbonaceous chondrites. (17th July 2022) - Yesiltas, Mehmet; Kebukawa, Yoko; Glotch, Timothy D.; Zolensky, Michael; Fries, Marc; Aysal, Namik; Tukel, Fatma S.
Abstract: Ungrouped carbonaceous chondrites are not easily classified into one of the well‐established groups due to compositional/petrological differences and geochemical anomalies. Type 2 ungrouped carbonaceous chondrites represent a very small fraction of all carbonaceous chondrites. They can potentially represent different aspects of asteroids and their regolith material. By conducting a multitechnique investigation, we show that Queen Alexandra Range (QUE) 99038 and Elephant Moraine (EET) 83226 do not resemble type 2 carbonaceous chondrites. QUE 99038 exhibits coarse‐grained matrix, Fe‐rich rims on olivines, and an apparent lack of tochilinite, suggesting that QUE 99038 has been metamorphosed. Its polyaromatic organic matter structures closely resemble oxidized CV3 chondrites. EET 83226 exhibits a clastic texture with high porosity and shows similarities to CO3 chondrites. It consists of numerous large chondrules with fine‐grained rims that are often fragmented and discontinuous and set within matrix, suggesting a formation mechanism for the rims in a regolith environment. The kind of processes that can result in such chemical compositions as in QUE 99038 and EET 83226 is currently not fully known and clearly presents a conundrum. Tarda is a highly friable carbonaceous chondrite with close resemblance to Tagish Lake (ungrouped C2 chondrite). It comprises different types of chondrules (some with Fe‐rich rims), framboid magnetite, sulfides, carbonates, and phyllosilicate‐ and carbon‐rich matrix, and is consistent with being an ungrouped C2 chondrite.